Tables, Formulas and Exercises with Key for Biometrics - Kraner Šumenjak, Tadeja; Sem, Vilma (2018)
This publication includes some materials we use in the one semester bachelor course entitled Biometrics,  at the Faculty of Agriculture and Life Sciences. In the last few years, several foreign students came to study at the University of Maribor. A certain number of them came to study at the Faculty of Agriculture and Life Sciences, and because the foreign students are not able to follow the lectures in Slovene, we organized lectures in English. Since there was no learning material in English that would deal with the basics of statistics through solving real problems from agriculture using the statistical program SPSS, we decided to translate and publish these materials, and thus make them more available.
Keywords: biometrics; statistical tables; statistical formulas; SPSS; exercises